Optimalisasi Kapasitas Apron Bandar Udara Internasional Minangkabau Padang - Irfan; Mutmainnah, Nurul (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Minangkabau International Airport has one apron and one hangar. Apron has 7 parking stands with number of parking stand are 1, 2, 3, 4, 5, 6A, and 7. Parking stands 1 and 7 are dedicated to light aircraft. Parking stand 2 is devoted to International flights. The existence of parking 1 and 7 is less than optimal because the type of light aircraft rarely operates. If there is a peak hour the number of aircraft that will be parked in the apron is less able to be served based on the available parking stand so that the aircraft is often held at the alpha taxiway, this affects the passenger's time value and the cost value for the airline. The purpose of this research is to analyze the optimum apron capacity at Minangkabau International Airport, Padang. The research method is done through parking stand analysis on traffic arrangement in movement area through description of parking index analysis, parking duration, and parking accumulation at peak hour compared to available apron capacity and determined slot time. Optimization of aircraft parking (apron) Minangkabau international airport, padang can be done with the reduction of parking booth from 7 to 6 with the dimensions of medium aircraft, and emphasize the airline operators to remain consistent on the slot time set or propose revision of slot time at spare time